Profitability, efficiency and comparative advantage of African cattle meat and milk production: The case of trypanotolerant village cattle production - Itty, P. (Wiley, 1996)
Trypanosomiasis is a major constraint to increased food production in Africa as it limits livestock production and mixed farming over an area of 10 million km2. The use of African trypanotolerant breeds of cattle is one approach to control trypanosomiasis that is being given increasing attention.This paper examines under what circumstances trypanotolerant village cattle enterprises can be economically viable in regions of origin and areas of introduction. On-going production is analysed in four countries using cost-benefit analyses. Comparative advantage and subsidies received are also estimated. Results indicate that resources for trypanotolerant cattle production are efficiently allocated as the sector has a comparative advantage and contributes effectively to the national welfare. Financial returns to producers are attractive and by comparing social and private prices important constraints are identified to improve profitability.